The wedding date - Kilner, Clare; Messing, Debra 1968-; Mulroney, Dermot 1963-; Adams, Amy 1974-; Davenport, Jack 1973-; Parish, Sarah 1968-; Curtis, Oliver; Neely, Blake 1969-; Young, Liz (Viva Video, Inc., 2005)
Kat Ellis is determined to attend her younger sister's wedding with a date. Rather than face the ridicule of her family, and in order to show up her ex-fiance, she resorts to the Yellow Pages to find an escort.